2011
DOI: 10.1007/s12088-011-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Azo Dye (Orange MR) by an Autochthonous Bacterium, Micrococcus sp. DBS 2

Abstract: Soil and sediment samples obtained from Orange MR dye contaminated habitat were screened for heterotrophic bacterial population. The heterotrophic bacterial density of dye-contaminated soil was 2.14 9 10 6 CFU/g. The generic composition of heterotrophic bacterial population was primarily composed of 10% of Proteus sp., 15% Aeromonas sp., 20% Bacillus sp., 25% Pseudomonas sp. and 30% Micrococcus sp. The bacterial strain that decolorized the azo dye Orange MR up to 900 ppm was identified as Micrococcus sp. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…As mentioned previously, additional carbon and nitrogen sources, and a pH value in the range of 5 to 7, generally have a positive influence on decolourization efficiency (Chen et al 2003;Meerbergen et al 2018;Moosvi et al 2005;Rajee and Patterson 2011;Sawhney and Kumar 2011;Solis et al 2012).…”
Section: Dye Mixture Removal By Mixed Bacterial Culturesmentioning
confidence: 76%
See 1 more Smart Citation
“…As mentioned previously, additional carbon and nitrogen sources, and a pH value in the range of 5 to 7, generally have a positive influence on decolourization efficiency (Chen et al 2003;Meerbergen et al 2018;Moosvi et al 2005;Rajee and Patterson 2011;Sawhney and Kumar 2011;Solis et al 2012).…”
Section: Dye Mixture Removal By Mixed Bacterial Culturesmentioning
confidence: 76%
“…It is worth emphasizing that yeast extract (the growth medium component used) is considered essential to the regeneration of important factors such as NADH, which acts as an electron donor for the reduction of dye bonds. Rajee and Patterson (2011) showed that the highest efficiency of decolourization of orange MR by Micrococcus sp. (80%) was reached when pH = 6.…”
Section: Dye Mixture Removal By Pure Bacterial Culturementioning
confidence: 99%
“…The use of non-conventional, economical sources as precursors for activated carbon has been proposed to achieve the cost-effectiveness in the application. As previously stated, adsorption is a non-destructive method in which there is only the change in the phase of the removed impurities and, therefore impose further problems in the form of sludge [121][122][123][124]. The high cost also necessitates the adsorbent regeneration.…”
Section: Sonolysis Processmentioning
confidence: 99%
“…As the extent of decolouration is influenced by the pH of the media, pH also affects the colour of the solution and the solubility of the dye. Candida tropicalis adsorbs 45% of Basic Violet 3 at pH 3, 85% at pH 4 and 33% at pH 9 [83]. Micrococcus sp.…”
Section: Influence Of Salinity Dye Concentration Ph Temperature Anmentioning
confidence: 99%